Environmental Crimes in Ethiopia - Mwebaza, Rose; Mwanika, Philip Njuguna; Wonndemagegnehu, Wondowossen Sintayehu (INSTITUTE FOR SECURITY STUDIES, 2009)
"This study sets out to examine this complex question by determining what constitutes an environmental crime in Ethiopian jurisprudence.This will be done by examining the legal and institutional regime for combating environmental crimes. The study also examines the main perpetrators of environmental crime in Ethiopia and the main enforcement mechanisms that are in place to deal with the perpetrators. Finally, the study examines the capacity needs that have to be addressed to enhance the enforcement of environmental crimes in Ethiopia."